2014
DOI: 10.5665/sleep.3562
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Objectively and Subjectively Measured Sleep Quality with Subsequent Cognitive Decline in Older Community-Dwelling Men: The MrOS Sleep Study

Abstract: Among older community-dwelling men, reduced sleep efficiency, greater nighttime wakefulness, greater number of long wake episodes, and poor self-reported sleep quality were associated with subsequent cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(123 citation statements)
references
References 47 publications
4
101
5
1
Order By: Relevance
“…These symptoms are of particular concern in older subjects, because they may be misinterpreted as symptoms of dementia/mild cognitive impairment (MCI) (Roth and Ancoli‐Israel, 1999). There is a strong association of objectively and subjectively measured sleep quality with subsequent cognitive decline (Osorio et al, 2011; Blackwell et al, 2014). …”
Section: Melatonin In the Treatment Of Circadian Rhythm And Sleep Dismentioning
confidence: 99%
“…These symptoms are of particular concern in older subjects, because they may be misinterpreted as symptoms of dementia/mild cognitive impairment (MCI) (Roth and Ancoli‐Israel, 1999). There is a strong association of objectively and subjectively measured sleep quality with subsequent cognitive decline (Osorio et al, 2011; Blackwell et al, 2014). …”
Section: Melatonin In the Treatment Of Circadian Rhythm And Sleep Dismentioning
confidence: 99%
“…Among the 27 studies identified for the meta-analysis, there were 8 cross-sectional, 31,37,44-49 1 case-control, 50 2 retrospective cohort, 33,51 and 16 prospective cohort 32,34,36,[38][39][40][52][53][54][55][56][57][58][59][60][61] (Table 1). Of these, 15 were considered to be of high quality, 10 were of medium quality, and 2 were of low quality.…”
Section: Design and Qualitymentioning
confidence: 99%
“…Table 1 shows the general characteristics of the included studies. Seven studies [10,11,35,37,38,40,41] involved cognitive impairment, 2 studies involved dementia [36,39] , and 1 study involved both cognitive impairment and dementia [42] . The included studies were published between 2009 and 2015, spanning 6 years.…”
Section: Characteristics Of Studies Included In the Final Analysismentioning
confidence: 99%